Associations of MEG3 rs7158663, rs4081134 gene variants and Ki-67, p53, CK18 immunohistochemical markers with clinical features of pituitary neuroendocrine tumors - Zaliunas, Balys Remigijus; Pileckaite, Enrika; Duseikaite, Monika; Makstiene, Jurgita; Poskiene, Lina; Rovite, Vita; Wu, Sheng-Nan; Tamasauskas, Arimantas; Liutkeviciene, Rasa (Frontiers in Endocrinology, 2025)
AimThis study aimed to determine the associations of MEG3 rs7158663, rs4081134 gene variants, as well as the immunohistochemical markers Ki-67, p53, and CK18, with the clinical features of pituitary neuroendocrine tumors (PitNETs).MethodsThis case-control study included 340 individuals who were divided into two groups: a control group (n=220) and a PitNETgroup (n=120). DNA was isolated from the venous blood of study participants by the leukocyte salt precipitation method. Real-time polymerase chain reaction was used for the MEG3 rs7158663, rs4081134 single nucleotide variants genotyping. Immunohistochemical analysis of Ki-67 labeling index and p53 protein biomarkers was performed using the automated Ventana BenchMark ULTRA PLUS staining system, following the manufacturer’s recommendations. CK18 immunostaining was conducted with the Dako Omnis staining system, following the manufacturer’s recommendations. Monoclonal antibodies SP6, DO-7, and DC-10 were used to detect Ki-67 labeling index, p53, and CK18, respectively. Statistical data analysis was performed using the “IBM SPSS Statistics 30.0” program.ResultsGenotype and allele frequencies of MEG3 rs7158663 and rs4081134 variants showed no significant differences between healthy controls and PitNET patient groups. Additionally, no associations were found between either MEG3 variants and PitNET recurrence, size, invasiveness, and functional status. Ki-67 labeling index (>3% vs. ≤3%) showed no significant differences with any clinical feature of PitNETs (recurrence, size, invasiveness, functional status). In contrast, the p53 H-score was significantly higher in macroadenomas than in microadenomas (median 27 vs. 16; p=0.008). Additionally, invasive pituitary adenomas showed a higher p53 H-score compared with non-invasive tumors (median 27 vs. 20; p=0.018). Negative CK18 immunostaining was significantly more frequent in invasive than non-invasive PitNETs (44.4% vs. 13.3%; p < 0.001) and in non-functioning compared to functioning adenomas (42.0% vs. 18.4%; p=0.011). No significant associations were found between either MEG3 variant and Ki-67 LI, p53 H-score, or CK18 immunohistochemical reactions.ConclusionsThis study found that a higher p53 H-score was significantly associated with larger PitNET size and invasiveness. Negative CK18 staining was associated with non-functioning and invasive PitNETs. P53 expression and CK18 status may serve as useful prognostic markers in PitNETs.